Respuesta :

Answer:

[tex]y=(x+2)(x-3)[/tex]

Step-by-step explanation:

Given: [tex]y=x^2-x-6[/tex]

To find: a factored form of the given equation

Solution:

The equation [tex]y=ax^2+bx+c[/tex] can be written in factored form as [tex]y=a(x-r_1)(x-r_2)[/tex].

To find the x-intercepts, put [tex]y=0[/tex].

Graph of the equation [tex]y=a(x-r_1)(x-r_2)[/tex] represents a parabola.

[tex]y=x^2-x-6\\=x^2+(-1)x-6\\=x^2+(-3+2)x-6\\=x^2-3x+2x-6\\=x(x-3)+2(x-3)\\=(x+2)(x-3)\\\Rightarrow y=(x+2)(x-3)[/tex]